Investigating restaurant customer complaints in Polokwane Malls, Limpopo Province - Phaswana, Tinyiko Patience (My University, 2017)
The research was qualitative, where groups of restaurants managers/owners were interviewed in the three Polokwane Malls namely Limpopo Mall, Savannah Mall and Mall of the North. The purpose of the interviews was to find out what customers complain about in restaurants. To find how the customers in restaurants lodge their complaints; how the businesses deal with complaints; how customers bring forth their complaints in different ways; and to identify which groups complain the most. Further, to find out how restaurant owners handle customer complaints and to whom customers lodge those complaints, and the ways which restaurants use to respond to the customers’ complaints. The research results show that restaurant customers complain mostly verbally to the managers. Females are the ones complaining more than their male counterparts. Levels of education make no difference to how customers complain. Waiters need to render quality service as product knowledge is not the only product customers prefer; they actually value service more. The study recommends that restaurants need to pay careful attention to services such as a clean eating area to avoid complaints as most complaints come about this area; verbal and nonverbal skills of employees should be developed in order to avoid complaints from customers. Managers should be equipped to handle customers’ complaints as they are the people to whom such complaints are addressed and waiters/waitress should be made aware that customers are important and their complaints are always valued in the business in order to improve service
Thesis (MBA.) --University of Limpopo, 2017
Keywords: Restaurant customers; Customer complaints; Polokwane Malls; Customer complaints